STUDENTS PERCEIVED IMPACT ON THE USE FREE WRITING IN EFL CLASSROOM - Nurul Aini; Ghovind Yusuf Prasetyo; M. Wildan Fasihuddin (English Language Teaching Journal, 2023)
Writing is skill that important to owened by learners because when learners want to writing education essay or education home work they must writing correctly. This study analyze students perception of the use free writing in EFL classroom that to improve writing skill. This research is to know students preception of use free-writing on EFL Classroom. The research usa a descriptive quantitative and using quisionaire to data collection that consist of fouftheen question as the research instrument. In this reseacher, reseacrher get 26 EFL students as the respondent from EFL students of English Education study program at Institut Agama Islam Negeri Kediri. The results of this study show that participants had positive responses toward free writing in the class. Participants apparently felt that free writing was an effective way to teach writing, helping them improve their writing and stay motivated Their feedback and responses indicate general agreement to free writing as a beneficial teaching strategy.